Première observation de l'éponge introduite et invasive Celtodoryx ciocalyptoides (Burton, 1935) (Porifera : Coelosphaeridae) dans le port du Havre (Manche) - Berno, A.; Dancie, C.; Pinsivy, L.; Corthésy, D.; Breton, G. (Hydroécologie Appliquée, 2016)
The aim of this paper is to notice a first occurrence in the Eastern English Channel and the introduction in the port of Le Havre of the sponge Celtodoryx ciocalyptoides (Burton, 1935), and to compare the population from Le Havre with the one from the North West Pacific (first description of the species), and the two populations that settled down in the 90’s in South Brittany (France) and the Oosterschelde (The Netherlands). The small population in the port of Le Havre has been found in 2014 at the rocky shore of a tidal dock, between + 1 m and - 4.8 m. The three European populations (Le Havre, South Brittany and Oosterschelde) and the Pacific population all developed in a paralic environment, defined as a transition zone between marine and continental systems. The introduction vector in Le Havre port is likely shipping and cannot be the importation of the spat of Crassostrea gigas (Thunberg, 1793) for farming, as suspected for the two previous European introductions of this species, given the lack of oyster farms in the vicinity.